2D weight function for quarter‐elliptical cracks in lug attachments. Issue 12 (11th June 2018) - Akbari, S.; Nabavi, S.M.; Saeidi Googarchin, H.
Abstract: The important role of lug attachments in mechanical structures makes them one of the most critical parts in the industries. Hence, the estimation of their fracture characteristic (ie, stress intensity factor) under various loadings is very crucial. Here, a 2D weight function is developed which not only calculate the stress intensity factors on each point of the front of quarter‐elliptical planar cracks in straight lugs but also could be used for those cracks subjected to 2D stress distributions. For this, a series of finite element analyses for a reference loading is conducted, and the weight function is subsequently extracted. Comparison between results obtained through the proposed weight function with those available in the literature reveals good agreements. The effects of various geometrical parameters have been studied on stress intensity factors which affirms the unique capability of the proposed 2D weight function in its applicability to a wide range of common lug geometries.